THE ANALYSIS OF STUDENTS’ PERCEPTIONS OF THE ONLINE LEARNING IN THE MIDST OF COVID-19 PANDEMIC AT STATE JUNIOR HIGH SCHOOL 16 PALEMBANG - Muhammad Ali (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2022)
The purposes ofthisstudywere to findouttheperceptions oftheonline learning in the midst of covid- 19 pandemic in the state of Junior High School 16 Palembang. The research was qualitative research. The subjects were thirty students of the seventh grade at the state of Junior High School 16 Palembang. Questionnaire, interview, and documentation were used to collect the data. The data were analyzed and interpreted through qualitative procedure. The findings indicatedthat the students had positive perception about efficient application used in online learning during the Covid-19 pandemic. Based on the results, it s hows that the application used in online learning during the midst of Covid-19 pandemic was efficient because the application can be an alternative way to conduct learning activity fromhome. While in s tudents’ perception about the most efficient application, most of them said that the most efficient, comfortable and economical application to use during the pandemic was WhatsApp. Keywords: perceptions, online learning, covid-19 pandemic